STUDY OF THERMAL DISTRIBUTION AND CLADDING GEOMETRY DURING LASER METAL DEPOSITION PROCESS USING FINITE ELEMENT ANALYSIS - Andrei Rusu; Alexandru Bunea; Liviu Daniel Ghiculescu (Nonconventional Technologies Review)
The paper deals with additive manufacturing process for coating and 3D printing metallic materials known in literature as laser cladding, laser melting deposition, laser engineering net shaping or direct energy deposition. In this process a melt pool was generated at the interaction of the laser beam with the blown powder guided through a copper nozzle. A 3D finite element model was established to simulate laser cladding process taking into account heat transfer in solids and geometry deformation modules from COMSOL Multiphysics software. A time-dependent study was conducted to manage the computational time of the numerical model. Boundary conditions were established by introducing a Gaussian distribution for the laser energy, as well as for the velocity and shape of the resulting track. Additionally, the thermal properties of the material under investigation were taken into account. Thermal analysis was conducted to determine the temperature history during the process using a heat transfer module, while the dynamic shape of the molten zone was represented by a moving mesh based on a deformed geometry module.